Deixisek a gyermeknyelvben - Boronkai, Dóra (Kultúratudományi Szemle, 2024)
Deixis, one of the basic micro-level procedures of texts, has a significant role in structuring two- or more-participant conversations. Previous research on spontaneous and structured texts of adults’ conversation has shown that exophoric deixis are responsible for personal relationships and spatial and temporal conditions of the text. Auto- and heterodeixis also play a role in spatial condition representations. In addition to the aforementioned text types, endophoric discourse deixis can play a prominent role in spontaneous conversations. In dialogical texts, the current speaker always processes the textual world from their own aspect, therefore, the deictic elements are closely related to the speaker’s aspect, as well. As the speaker connects the referenced entity to the speech situation in deixis in such a way that the recipient can access it with the least mental effort, the different types of deixis are supposed to be represented in child language conversations as the main discourse organisers. This paper examines the different types of deixis, their most common means of expression, and their function in conversation structuring; the research was conducted on spontaneous child language and child-adult conversation of a 13962 textword corpus from 141 respondents.